Analisa Efektivitas Kerja Bulldozer Terhadap Pengisian Rangkaian di Area Stockpile OPB 4 PT. Bukit Asam, Tbk - Sarmidi, Sarmidi; Aken Derisman (SURYA TEKNIKA, 2023)
Heavy equipment is a tool that functions to transport or move materials in a large capacity and in a relatively short time. The use of heavy equipment is also a way to increase company productivity. One example of heavy equipment used by the east block of the PT. Bukit Asam Tbk is a Bulldozer. According to the penambang.com website, the Bulldozer is a crawler tractor that is useful for digging, displacing, pushing soil and pulling an object, which can be operated by rocky, hilly, and mud fields in various work sectors such as mining, construction, logging, industrial plantation forests (forestry) and plantations. This study aims to find out how to determine the effectiveness of bulldozer work, find out what factors affect the effectiveness of bulldozer work and find out the percentage of bulldozer work effectiveness and coal production results on the circuit in the OPB 4 PT stockpile area. Bukit Asam Tbk. Final results display data in the form of bulldozer working time tables and coal delivery report data as well as operating and working hours graphs and coal delivery charts.